Flourishing: health and welfare of young apprentices' of Ceará (Brazil) industry (Gestão & Regionalidade, 2016)
In order to assess the flourishing level in the work of young apprentices of Ceará (Brazil) industry, a survey was administeredto 309 young people using the Flourishing Scale at Work (EFLOT, in the Portuguese acronym). The research is characterizedas descriptive and exploratory with a quantitative approach. The results indicate no significant difference in the level of flourishingin the matters of gender, schooling, and family income. However, there is a difference in the four distinct industrialsectors, especially a significantly lower average in the food and beverage one. It was concluded that the young apprenticesdo not have a full flourishing stage in relation to their first job.